Auditoria Interna del Sistema de Gestión Empresarial y su contribución al Crecimiento Económico de Empresa Distribuidora PMA E.I.R.L. Chimbote, 2017 - Chupe Esquivel, Rosario Elizabeth (2019)
ABSTRACT The problem of the present investigation is centered in the internal audit to analyze its contribution to the growth of the company Distribuidora PMA EIRL through its business management system; Its main objective is to determine how the Internal Audit of the Business Management System contributes to the optimal economic growth of the PMA EIRL Distribution Company, Chimbote 2017; The methodology used is descriptive; its sample corresponds to 24 collaborators belonging to the headquarters of Chimbote; The research design is based on the Applied-Non-Experimental type and Documentary analysis has been used in Techniques and Instruments; direct observation; the interview and the application of questionnaires; The main result is that an internal control unit that improves the deficiencies that the company maintains to carry out control activities, risk assessments and subsequent monitoring of its operational processes has not been implemented, likewise the main conclusion is that the internal audit of the Business Management system is favorable to contribute to the economic growth of the PMA EIRL Distributor, because it would be executed as a guide to ensure that the internal controls carried out are adequate to mitigate the risks in the company; On the other hand, it is recommended to Management to take into account that the internal audit is an exam based on the established internal controls, where it is possible to measure and evaluate the effectiveness of the operations, so it becomes an important guide to execute to take corrective measures of the weaknesses and weaknesses of the company.